Anorectal Malformations Caused by Defects in Sonic Hedgehog Signaling - Mo, Rong (American Society for Investigative Pathology, 2001)
Anorectal malformations are a common clinical problem affecting the development of the distal hindgut in infants. The spectrum of anorectal malformations ranges from the mildly stenotic anus to imperforate anus with a fistula between the urinary and intestinal tracts to the most severe form, persistent cloaca. The etiology, embryology, and pathogenesis of anorectal malformations are poorly understood and controversial. Sonic hedgehog (Shh) is an endoderm-derived signaling molecule that induces mesodermal gene expression in the chick hindgut. However, the role of Shh signaling in mammalian hindgut development is unknown. Here, we show that mutant mice with various defects in the Shh signaling pathway exhibit a spectrum of distal hindgut defects mimicking human anorectal malformations. Shh null-mutant mice display persistent cloaca. Mutant mice lacking Gli2 or Gli3, two zinc finger transcription factors involved in Shh signaling, respectively, exhibit imperforate anus with recto-urethral fistula and anal stenosis. Furthermore, persistent cloaca is also observed in Gli2(−/−);Gli3(+/−), Gli2(+/−);Gli3(−/−), and Gli2(−/−);Gli3(−/−) mice demonstrating a gene dose-dependent effect. Therefore, Shh signaling is essential for normal development of the distal hindgut in mice and mutations affecting Shh signaling produce a spectrum of anorectal malformations that may reveal new insights into their human disease equivalents.